Ractopamine supplementation improves leanness and carcass yield, minimally affecting pork quality in immunocastrated pigs (Scientia Agricola, 2018)
This study was carried out to determine the combining effects of feeding up to 15 mg kg−1 ractopamine (RAC) to physically castrated (PC) pigs or those injected with an anti-GnRF vaccine (IC), on growth performance during suckling, weaning, growing and finishing phases. Out of a total of 1,160 male piglets, 50 % were surgically castrated at age 7, while 50 % underwent immunization against GnRF on the 103rd and 136th day of life. A completely randomized design, with two treatments (PC and IC), was used from the 1st until the 60th day of life. Afterwards, 792 animals, PC and IC, selected according to overall average weight (23.3 ± 0.69 kg) were allotted based on a completely randomized block design with a 2 × 4 factorial arrangement of treatments (castration categories × RAC levels) with 9 replications (11 animals) per main combination effect. IC growing pigs improved feed conversion due to lower average daily feed intake and higher average daily gain (ADG). During the finishing phase, both RAC and immunocastration increased body weight, but the effects were independent. RAC, on its own improved ADG and feed conversion. However, pigs fed 10 mg kg−1 RAC had higher blood lactate compared to those fed lower levels, suggesting that these animals were more susceptible to stress. Muscle depth was influenced only by RAC, whereas fat thickness was lower for IC. Lean meat increased and fat decreased in the shoulder and belly of IC; RAC had a positive effect on belly lean meat only. Either immunocastration or RAC inclusion (at least 5 mg kg−1) promoted muscle gain and fat reduction in pig carcass, adding value to pork.